Adsorption Dye in Batik Wastewater using Biomass Adsorbent : a State of the Art Review - Retno Dwi Nyamiati; Vera Listiawati; Galang Ariyuda (Formosa Journal of Applied Sciences, 2023)
In this article, we study several research about optimizing the adsorption of harmful compounds contained in batik dye liquid waste using activated carbon. The employment of naphthalene as a chromogenic agent in the batik industry introduces a significant quandary by contributing to water pollution through effluent discharge. Noteworthy efforts have been made by certain industries, employing activated carbon to mitigate the presence of Pb and Cr attributable to naphthalene. The principal objective of this exposition is to consolidate insights into the sequestration of perilous dyes within batik industry effluents, leveraging various forms of natural activated carbon. The kinetics of the adsorption process will be quantified utilizing the appropriate kinetic order formula, while equilibrium data will be scrutinized through reaction isotherms employing diverse models.